North Atlantic Subtropical Mode Water properties: intrinsic and atmospherically forced interannual variability - O. Narinc; T. Penduff; G. Maze; S. Leroux; J.-M. Molines (Ocean Science)
This study investigates the contributions of the ocean's chaotic intrinsic variability (CIV) and atmospherically forced variability to the interannual fluctuations in the North Atlantic Subtropical Mode Water (STMW) properties. Utilizing a 0.25° regional 50-member ocean–sea-ice ensemble simulation driven by an original surface forcing method and perturbed initially, the forced variability in STMW properties is estimated from ensemble mean fluctuations, while CIV is determined from deviations around the ensemble mean within each member. The model successfully captures the main features of STMW, showing correct agreement with observation-based ARMOR3D data in terms of location, seasonality, mean temperature and volume, as well as interannual variance of STMW's main properties. CIV significantly impacts STMW, explaining 10 %–13 % and 28 %–44 % of the interannual variance of its geometric and thermohaline mean properties, respectively, with a maximum imprint on STMW temperature. Observation-based and simulated intrinsic-to-total variance ratios are mostly consistent, dispelling concerns about a signal-to-noise paradox. This study also illustrates the advantages of ensemble simulations over single simulations in understanding oceanic fluctuations and attributing them to external drivers, while also cautioning against overreliance on individual simulation assessments.